Dyanamics Model of Finacial Analyst Impact in Nigerian Stock Exchange - Akpienbi, Isaac Oritsejubemi; Ezra, Emmanuel Tanto (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Mathematical model was developed in this paper in the form of SEIR model to study NSE market dynamics of the interaction between potential investor, conservative investor, equity analyst and quitting investor in Nigeria. The equilibrium points of the model were determined and their stability analysis was performed. The research investigates the stability of the free NSE financial market equilibrium in Nigeria, revealing that it is locally and globally asymptotically stable. Local stability analysis shows the market's ability to recover from small perturbations, while global stability analysis confirms that it will stabilize over time regardless of the magnitude of disturbances. These findings provide real-life investors with confidence in the Nigerian financial market's resilience to both minor and significant shocks. The assurance that the market will return to equilibrium despite fluctuations in stock prices, trading volumes, or larger economic events encourages long-term investments and participation in the NSE.